Retrospective evaluation of the induction of emesis with apomorphine as treatment for gastric foreign bodies in dogs (2010‐2014): 61 cases. Issue 2 (19th February 2020) - Zersen, Kristin M.; Peterson, Nathan; Bergman, Philip J.
Abstract: Objective: To determine the success rate and complications associated with inducing emesis in dogs that have ingested foreign material. Design: Retrospective case series, 2010–2014. Setting: Private practice and referral center. Animals: Sixty‐one client‐owned dogs that had emesis induced for the treatment of ingestion of foreign material. Interventions: None. Measurements and Main Results: Emesis was successfully induced in 59 of 61 (97%) dogs administered an emetic. Of those 59 dogs, 46 (78%) produced the foreign body. There were no complications reported in any of the dogs in which emesis was successfully induced. Dogs in which emesis was successfully induced were likely to produce the foreign body ( P  = 0.01). Conclusion: Based on the results of this study, emesis appears to be a safe and effective means for the removal of certain gastric foreign bodies in dogs.